Handbook of biomaterials biocompatibility - Mozafari, Masoud (Woodhead Publishing, 2020)
Handbook of Biomaterials Biocompatibility is a systematic reference on host response to different biomaterials, taking into account their physical, mechanical and chemical properties. The book reviews recent progress in the design and study of biomaterials biocompatibility, along with current understanding on how to control immune system response. Sections provide the fundamental theories and challenges of biomaterials biocompatibility, the role of different biomaterials physicochemical surface properties on cell responses, cell responses to different physicochemical properties of polymers, ceramics, metals, carbons and nanomaterials, and biomaterials in different tissues, such as the cardiac, nervous system, cartilage and bone. This resource will be suitable for those working in the fields of materials science, regenerative engineering, medicine, medical devices and nanotechnology.
Keywords: Biomedical materials.; Biocompatibility.; Foreign-body reaction.; elektronické knihy; electronic books